PURIFICATION OF THE 28KDA CATHEPSIN L FROM FASCIOLA HEPATICA - Arias, Luis (2015)
This work aims to isolate the 28KDa proteinase from the parasite Fasciola hepatica (Linnaeus, 1758). This cysteinyl protease was purified by classical methods such as the ammonium sulphate precipitation, G-25 and G-75 gel filtration chromatographies, affinity chromatography with thiol sepharose 4B and SDS-PAGE 12% electrophoresis. The enzymatic activity of Cathepsin L was monitored in each step of purification using a specific substrate. The cysteine proteinase was observed as a pure and homogenous band in the SDS-PAGE gel. The recovery percentage was 12.7%, with a specific activity of 337,500 umol, min-1 mg-1 and a purification factor of the enzyme of 260. Using this simple scheme of purification we purified to homogeneity the cathepsin L of 28KDa from the regurgitate in an effective way compared with other alternative methods. The amount of protein obtained was 0.032 mg·mL-¹. The enzyme showed as a homogenous band during the electrophoresis in polyacrylamide gel with 12.5% SDS-PAGE and the molecular weight was 28 kDa according to its relative mobility.